Evaluación de diferentes medios de consevación de semilla de frijol (phaseolus vulgaris) variedad huasca poroto en la E.E. El porvenir San Martín - Castillo Santa María, Bessy (2000)
The development of the present work was carried out in the E.E. " El Porvenir"-INIA in Juan's War distticl, county and department of San Marlln among March 04 al the 08 of 1 998. He she had as maln objectve to evaluate lhe effect of the dlfferent means (natural and chemlcal) in the conservation of the seed Huasca Poroto. Using the design completely to the orange blossom with 12 treatments and 3 repetltlons wlth Y2 kg of bean seed Huasca Poroto to a temperature average of 27ºC belng evaluated every 15 days the established parameters, for their action Zabrotlles subfasciatus has more than enough (Boh.) Being obtained that both compounds (chemical and natural) they had an excellent inilial and residual effect malntaining the grain free of Infestación durlng the fif'st 15 days, where the T1 (Potyethylene wlth Malathlón) H was one of the most effeclive compounds in smaller proportion. The smallest economic cost was of the employment of Bag of Paper - T2 (Witness) wlth SI. 32, 13 nuevos soles.